2021
DOI: 10.5530/ijmedph.2021.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Children and Adults: A Bibliometric Assessment of Global Publications

Abstract: The paper presents a analysis of quantitative and qualitative dimensions of global research output (3488 records) on "Impact of COVID-19 on Children and Adolescents" , based on indexed publications in Scopus database. The global publications on this theme averaged 8.31 citations per paper. About 1.49% share of its total publications in this area received external funding support. The 145 countries partcipitated in global research output on "Impact of COVID-19 on Children and Adults" , of which the top 10 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The results of this part of the research are in line with Hossein (2020), Surulinathi et al (2020), Abideen et al (2020), Sachini et al (2021), Chiu et al (2004), Sa’ed (2016), Shamsi et al (2020), Krishnamurthy et al (2020), Gupta et al (2021), Okhovati and Arshadi (2021) and Sa'ed (2021). Hossein (2020) presented the network of authors contributing to the COVID-19 research, which indicates networks with almost passive collaborations and identified “Mahase, E” as the most prolific researcher.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The results of this part of the research are in line with Hossein (2020), Surulinathi et al (2020), Abideen et al (2020), Sachini et al (2021), Chiu et al (2004), Sa’ed (2016), Shamsi et al (2020), Krishnamurthy et al (2020), Gupta et al (2021), Okhovati and Arshadi (2021) and Sa'ed (2021). Hossein (2020) presented the network of authors contributing to the COVID-19 research, which indicates networks with almost passive collaborations and identified “Mahase, E” as the most prolific researcher.…”
Section: Discussionsupporting
confidence: 81%
“…Oh and Kim (2020) revealed that the American (USA) and Australian nursing journals had published the most significant number of papers on COVID-19. Gupta et al (2021) claimed that the USA, UK, Italy and China published the most articles on COVID-19 in children and adolescents. Espinosa et al (2021) concluded that Chile had published the most original articles in Latin America and the Caribbean (LAC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations